Mild diabetes: long-term effects on gastric motility evaluated in rats - Hauschildt, Andrieli T.; Corá, Luciana A.; Volpato, Gustavo T.; Sinzato, Yuri K. [UNESP]; Damasceno, Débora C. [UNESP]; Américo, Madileine F. (My University, 2018)
Moderate hyperglycaemic levels seem to be related to abnormal gastric motility in diabetes mellitus. However, experimental models designed to evaluate the relationship between motility and diabetes over time are not yet well established. Our objective was to investigate the long-term effects of mild diabetes on gastric motility in rats. Newborn male rats received streptozotocin (mild diabetes groups – MD) or vehicle (control groups – C), and both groups were evaluated after 3 (C3 and MD3) and 6 months (C6 and MD6) postinduction. Mild diabetic animals (MD3 and MD6) showed moderately elevated blood glucose and decreased insulin levels compared with control (C3 and C6). Insulin secretion was enhanced in MD6 compared with MD3, most likely due to partial β-cell regeneration indicated by HOMA-β. In HOMA-IR, it was noticed that MD6 animals had impaired insulin response compared with MD3. Gastric emptying was faster, amplitude of contraction was stronger in MD6 compared with MD3, and in both groups, the differences were significant when compared with control animals. A significant abnormal rhythmic index was calculated for the mild diabetic groups, despite unchanged mean frequency of contraction. In conclusion, despite increased insulin levels over time, constant levels of moderate hyperglycaemia are also related to abnormal gastric motility and impairment of gastric function.
Keywords: experimental diabetes; gastric emptying; moderate hyperglycaemia; motility disorders; stomach contractions